Ecomechanics of black corals (Cnidaria: Anthozoa: Hexacorallia: Antipatharia): A comparative approach. Issue 4 (5th October 2021) - Dugauquier, Jean‐Marc; Godefroid, Mathilde; M'Zoudi, Saloua; Terrana, Lucas; Todinanahary, Gildas; Eeckhaut, Igor; Dubois, Philippe
Abstract: Mechanical properties of the skeleton of four antipatharians (the whip species Cirrhipathes anguina and Stichopathes cf. maldivensis, and the branched species Cupressopathes abies and Cupressopathes cf. pumila ) living in shallow waters off the southwestern coast of Madagascar were investigated using a three‐point bending test. The Young's modulus did not differ according to species but was significantly higher in the distal segment of colonies, compared with the basal and median segments. By contrast, the flexural stiffness was significantly higher in whip species compared with branched ones, and in the whip species, flexural stiffness was higher in the basal segment compared with the other two segments, an observation consistent with a specific adaptation of the species to a strong current environment. Although both species cohabit identical flow conditions, whip species are able to maintain their stalk in vertical position, whereas branched species can readily bend over. This suggests that the specific flexural stiffness is linked to contrasting feeding strategies of species with different morphologies in a similar strong current environment.